Mental health issues experienced by jail inmates in Texas: An overview of diagnostic problems - Gerber, Jurg; Cho, Ahram (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The main purpose of the article is to show selected aspects of prisoners’ mental health in the United States using the example of the state of Texas. The article indicates the nature and scope of needs in the area of inmates’ mental health in various correctional units and shows some aspects of the diagnosis problems. The authors analyze the reasons for the transfer of responsibility for mental health of prisoners sentenced to the administration of correctional facilities, especially jails. The article also shows the needs of the Prison Administration regarding convicts’ mental health training and classification systems for prisoners in Texas.
Keywords: zdrowie psychiczne osadzonych; diagnostyka problemów; problemy z zakładami karnymi w Teksasie